Characteristics of research with older people (over 65 years) in occupational therapy journals, 2013–2017. (18th May 2020) - Österholm, Johannes H.; Larsson Ranada, Åsa
Abstract: Background: A growing population of older people will require different types of occupational therapy services in the future. For occupational therapists to provide effective services and to optimize care, their practice must rely on high-quality evidence. Research is one important pillar of evidence-based practice. Therefore, it is important to examine the research published in occupational therapy journals, which guides practitioners in their work with clients. Aim: The overall aim of this study was to review research characteristics in articles with older persons as participants, aged over 65 years, with or without illness, diseases or disabilities, reported in occupational therapy journals during the period 2013–2017. Materials and methods: Data was collected from peer-reviewed occupational therapy journals and categorized in relation to research characteristics using descriptive statistics. Results: The findings show that most articles presented basic research, using quantitative design where the sources of data were instruments. Conclusion: The findings suggest that both qualitative and quantitative articles use appropriate sample sizes. However, descriptions of the studied populations are frequently unclear, which may affect the transferability and generalization of the results. Significance: In order to support practice, efforts are needed to develop research aims and questions that develop knowledge to embrace more than just basic research.